Application of the aqueous two-phase systems of ethylene and propylene oxide copolymer-maltodextrin for protein purification - Bolognese, Belén (2005)
In this study, the effect of several factors that govern the partitioning behaviour of three model proteins, such as bovine serum albumin, lysozyme and trypsin was analysed in a two-phase system formed by maltodextrin and a copolymer of ethylene and propylene oxides. The protein partition coefficient (K r) showed to be very sensitive to temperature changes, protein molecular weight, pH medium and the lyotropic ion presence. The phase diagram obtained for these novel polymer-polymer two-phase systems shows two phases with high polymer concentrations. The maltodextrin is enriched in the bottom phase while the copolymer of ethylene and propylene oxides is found in the upper phase. Since this copolymer is thermoreactive, the upper phase can be removed and heated above the copolymer's cloud point resulting in the formation of a new two-phase system with a lower water phase, containing the target protein and an upper copolymer-rich phase. Our results show that systems formed by maltodextrin and a copolymer of ethylene and propylene oxides may be considered as an interesting alternative to be used in protein purification due to their low cost, and also because they offer a viable solution to problems of polymer removal and recycling.